Single session thinking and practice in global, cultural, and familial contexts : expanding applications - Hoyt, Michael F.; Young, Jeff (Clinical psychologist); Rycroft, Pam (New York : Routledge, Taylor & Francis Group, 2021)
"Single Session Thinking and Practice teaches readers how to implement single session approaches by encouraging practitioners and clients to collaborate in making the most of every encounter. Single session/one-at-a-time approaches are applicable in a multitude of settings, including clinics, private offices, medical centers, and student counseling services - and can be used both in person and online. Leading international figures and those practicing on the front lines provide guidance for conducting SST in a variety of contexts. Chapters feature descriptions of theoretical underpinnings, pragmatic clinical examples, cross-cultural applications, research findings, service delivery models, and implementation tips. This text will be an instant and essential reference for anyone in the fields of brief therapy, casework, and healthcare, as well as walk-in and by-appointment single session services"--
List of FiguresList of TablesAbout the ContributorsAcknowledgmentsForeword by Moshe TalmonSECTION 1: Editors' Introduction1. Single Session Thinking and Practice Going Global--SECTION 2: Orientations: Single Session Thinking2. The Hope and Joy of Single-Session Thinking and Practice--3. Translating Single Session Thinking into Practice--4. An Open Invitation to Walk-In Therapy: Opening Access to Mental Health Care--5. Single Session Family Consultation--6. The Vital Role of the Therapist's Mindset--7. Gradually and Suddenly: What Zen Teaches Us about Change in SST--SECTION 3: Implementation: Single Session Practice 8. Implementing Single Session Thinking in Public Mental Health Settings in Queensland: Part 1. Introducing Single Session Family Consultations into Adult Inpatient and Community Care--9. Implementing Single Session Thinking in a Public Mental Health Settings in Queensland: Part II. Adapting and Integrating Single Session Therapy into an Acute Care Setting--10. One-Off Sessions to Address a Waitlist: A Pilot Study--11. The Story of the Eastside Family Centre: 30 Years of Walk-In Single Session Therapy--12. Embedding Single Session Family Consultation in a National Youth Mental-Health Service: Headspace--SECTION 4: Single Session Thinking and Practice in Different Clinical Contexts 13. Introducing Single Session Therapy at a University Counseling Center--14. Sign Up, Meet Up, Speak Out: Single Sessions in the Context of Meet-Up Groups--15. Making the Leap with Couples in Sweden: One-at-a-Time Mindset in Action--16. Complex and Challenging Issues in SST: Reflections on the Past and Learnings for the Future--17. Strengthening Family Resilience Using a Single Session Mindset: Supporting Families Following a Child's Diagnosis of Autism--18. Single Session Approaches with Infants: A Collaborative Single Session Model--19. Single Session Therapy for People with a New HIV Diagnosis: Achieving a Positive Result--SECTION 5: Applications in Cross-Cultural/Non-Western Contexts 20. Following the River's Flow: A Conversation about Single Session Approaches with Aboriginal Families--21. Hope in Remote Places: Single Session Therapy in Indigenous Communities in Canada--22. Single Session Family Consultation Implementation in Aotearoa New Zealand: Cultural Considerations--23. Single Session Team Family Therapy (SSTFT) in China: A 7-Step Protocol for Adapting Western Models in Eastern Contexts--24. Single Session Ericksonian Strategic Hypnotherapy for Disasters in Mexico--SECTION 6: Single Session Thinking and Practice with Families25. Families at First Sight: Practice Innovations Towards Making Family SST More Friendly and Effective--26. Embedding the "Family Oriented Collaboration Utilising Strengths" (FOCUS) Clinic in a Child and Youth Mental Health Service and University Partnership--27. Integrating a Single Session Family Therapy Approach in Two Child and Youth Mental Health Services--28. Single Session Therapy with Those Affected by Gambling: Listening to Clients and Their Therapeutic Counselors--29. Single Session Family Consultation with Adults Affected by Eating Disorders--30. Collaborative First Meetings with Young People Who Have Eating Disorders and Their Families--SECTION 7: Editors Ćonclusion 31. Single Session Thinking and Practice: Themes, Lessons, and a Look Toward the Future--Index
OCLC-licensed vendor bibliographic record.
Keywords: Single-session psychotherapy; Brief psychotherapy; Psychotherapy; MEDICAL / Psychiatry / General; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Psychotherapy / Counseling